A comparison of edge-preserving approaches for differential interference contrast microscopy. (28th July 2017) - Rebegoldi, S; Bautista, L; Blanc-Féraud, L; Prato, M; Zanni, L; Plata, A
Abstract: In this paper we address the problem of estimating the phase from color images acquired with differential-interference-contrast microscopy. In particular, we consider the nonlinear and nonconvex optimization problem obtained by regularizing a least-squares-like discrepancy term with an edge-preserving functional, given by either the hypersurface potential or the total variation one. We investigate the analytical properties of the resulting objective functions, proving the existence of minimum points, and we propose effective optimization tools able to obtain in both the smooth and the nonsmooth case accurate reconstructions with a reduced computational demand.